Fostering Moral Resilience: Evaluating a High-Fidelity Ethics Simulation With Prelicensure Nursing Students in Their Practice as New Graduates - Forte, Kathy; Higgins, Melinda; Pentz, Rebecca D (Nurse educator, 2025)
Despite the high prevalence of moral distress in nursing, empirical evidence is lacking about the best educational approaches to foster moral resilience. This study evaluates the effectiveness of an ethics simulation in a prelicensure program, 6 months into nursing practice. We used an exploratory design, including 2 instruments and open-ended questions. One instrument measured moral distress, the other measured moral resilience. Alumni who participated in the simulation were compared to alumni who received didactic teaching only. Six months into practice, the quantitative data from this study did not show a statistical significance between those who received didactic training only and those who received a simulation, except for one element of the moral resilience scale (relational integrity), in which the control group had a higher score. Open-ended questions confirmed that alumni recognized the positive impact of the simulation in practice. Further study is needed to determine the best educational strategies for teaching ethics in prelicensure nursing programs, with a focus on improving retention and resilience in practice.